Pearls and Black Gold - Aboelela, Ayah (The Columbia Journal of Asia, 2022)
This short story is narrated by Marzuk, a 90-year-old Kuwaiti man, around the year 2008. He reflects on his life as a young man in what was then-called Kuwait Town during the 1930s, when the pearl fishing industry was declining. Without giving too much of the story away, the central conflict revolves around Marzuq’s inability to achieve his father’s desire, which is for him to find success in the pearl industry. It uses secondary sources on Kuwaiti history, as well as first-person primary source accounts of pearl driving on the Arabian/Persian Sea.